Ground-based observations of the auroral zone and polar cap ionospheric responses to dayside transient reconnection - J. A. Davies (Annales Geophysicae, 2002)
Observations from the EISCAT VHF incoherent scatter radar system in northern Norway, during a run of the common programme CP-4, reveal a series of poleward-propagating F-region electron density enhancements in the pre-noon sector on 23 November 1999. These plasma density features, which are observed under conditions of a strongly southward interplanetary magnetic field, exhibit a recurrence rate of under 10 min and appear to emanate from the vicinity of the open/closed field-line boundary from where they travel into the polar cap; this is suggestive of their being an ionospheric response to transient reconnection at the day-side magnetopause (flux transfer events). Simultaneous with the density structures detected by the VHF radar, poleward-moving radar auroral forms (PMRAFs) are observed by the Finland HF coherent scatter radar. It is thought that PM-RAFs, which are commonly observed near local noon by HF radars, are also related to flux transfer events, although the specific mechanism for the generation of the field-aligned irregularities within such features is not well understood. The HF observations suggest, that for much of their existence, the PMRAFs trace fossil signatures of transient reconnection rather than revealing the footprint of active reconnection itself; this is evidenced not least by the fact that the PMRAFs become narrower in spectral width as they evolve away from the region of more classical, broad cusp scatter in which they originate. Interpretation of the HF observations with reference to the plasma parameters diagnosed by the incoherent scatter radar suggests that as the PMRAFs migrate away from the reconnection site and across the polar cap, entrained in the ambient antisunward flow, the irregularities therein are generated by the presence of gradients in the electron density, with these gradients having been formed through structuring of the ionosphere in the cusp region in response to transient reconnection. Key words. Magnetospheric physics (magnetosphere-ionosphere interaction) – ionosphere (ionospheric irregularities; plasma density and temperature)